1989
DOI: 10.1111/j.1476-5381.1989.tb11854.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of capsaicin desensitization on the stimulatory effect of kinins, prostaglandins, biogenic amines and various drugs in guinea‐pig isolated atria

Abstract: 1 A simple desensitization protocol was set up using capsaicin and isolated, spontaneously beating atria of guinea-pigs to assess the possible participation of cardiac, capsaicin-sensitive, substance P (SP)-and calcitonin gene-related peptide (CGRP)-containing sensory nerve fibres, in the cardiac stimulatory effects of bradykinin (Bk), kallidin (Kd), 5-hydroxytryptamine (5-HT), histamine, prostaglandin E2 (PGE2), prostaglandin El (PGE1), prostaglandin F2., (PGF2Z), adrenaline (Ad), glucagon, nicotine and angio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…Previous work has indicated that 5-HT activates the 'efferent' function of capsaicin-sensitive sensory neurones. Evidence for this has been obtained indirectly by showing that at least part of the inotropic response produced by 5-HT in the guinea-pig isolated atrium is abolished by capsaicin pretreatment in vitro (Bernoussi & Rioux, 1989). Our present data confirm these previous findings.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Previous work has indicated that 5-HT activates the 'efferent' function of capsaicin-sensitive sensory neurones. Evidence for this has been obtained indirectly by showing that at least part of the inotropic response produced by 5-HT in the guinea-pig isolated atrium is abolished by capsaicin pretreatment in vitro (Bernoussi & Rioux, 1989). Our present data confirm these previous findings.…”
Section: Discussionsupporting
confidence: 90%
“…CGRP increases the force and rate of contraction in the guinea-pig isolated atrium and is considered the mediator of the inotropic response produced in this preparation by the activation of sensory nerves (Franco-Cereceda & Lundberg, 1985;Saito et al, 1986;Sigrist et al, 1986;Giuliani et al, 1989). Indirect evidence suggests that in the guinea-pig isolated atria, 5-HT can release CGRP from capsaicin-sensitive sensory nerves, since the inotropic response evoked by 5-HT is reduced by in vitro capsaicin desensitization (Bernoussi & Rioux, 1989). Recently, release of substance P by 5-HT has been shown from dorsal root ganglion neurones in culture (Vedder & Otten, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of the positive chronotropic effect of 5-HT in the guinea-pig have suggested that the response is not mediated by P-adrenoceptors, 5-HTI-like, 5-HT2 or 5-HT3 receptors (Walter et al, 1984;Dhasmana et al, 1988;Eglen & Whiting, 1989) but have failed to identify clearly the receptor involved. There is evidence to suggest that the 5-HT-induced positive inotropic response in guinea-pig atria is due to the release of calcitonin gene-related peptide (Bernoussi & Rioux, 1989;Tramontana et al, 1993) and that this effect is due to the stimulation of 5-HT3 receptors (Tramontana et al, 1993 …”
Section: Introductdonmentioning
confidence: 99%
“…Functionally, 5-HT has been shown both to stimulate and inhibit C-fibres to modulate efferent release of neuropeptides. In guinea-pig isolated atria (Bernoussi & Rioux, 1989) 5-HT3 receptors stimulate efferent neuropeptide release (Tramontana et al, 1993); however, in the rat and guinea-pig dura mater 5-HT receptor activation inhibits plasma extravasation indicating an inhibition of extracranial perivascular sensory fibres via 5-HTIB and 5-HTID receptors, respectively (Buzzi & Moskowitz, 1990;Matsubara et al, 1991).…”
Section: Introductionmentioning
confidence: 99%